Timing Decisions in Organizations: Communication and Authority in a Dynamic Environment - Grenadier, Steven R.; Malenko, Andrey; Malenko, Nadya (American Economic Review, 2016)
We consider a problem where an uninformed principal makes a timing decision interacting with an informed but biased agent. Because time is irreversible, the direction of the bias crucially affects the agent's ability to credibly communicate information. When the agent favors late decision making, full information revelation often occurs. In this case, centralized decision making, where the principal retains authority and communicates with the agent, implements the optimal decision-making rule. When the agent favors early decision making, communication is partial, and the optimal decision-making rule is not implemented. Delegation adds value when the bias is for early decision making, but not for late decision making. (JEL D21, D23, D82, D83)